The Role of Tourism, Technological Innovation, and Globalization in Driving Energy Demand in Major Tourist Regions - Ridwan, Mohammad; Akther, Afsana; Al Absy, Mujeeb Saif Mohsen; Tahsin, Muhtasib Sarker; Ridzuan, Abdul Rahim; Yagis, Onur; Mukhtar, K. P. Jaheer (International Journal of Energy Economics and Policy, 2024)
This extensive study explores the complex relationship between tourism, technological innovation, globalization, and energy use in leading tourist region consist of UK, USA, Mexico, Austria, France, Germany, Greece, Italy, and Spain from 1990 to 2019. The research examines the effects of key factors on energy consumption dynamics using the Marshallian Demand Function. The study utilized the Panel Autoregressive Distributive Lag Model (ARDL) in addition to Quantile Regression techniques to explore the intricate connections between the explanatory and dependent variables. The results highlight that increase in economic growth, technological innovation, and globalization increased energy consumption in the prominent tourist region. On the other hand, tourism and trade openness were discovered to have an inverse correlation with energy consumption. This study provides valuable insights into the intricate dynamics that influence energy consumption patterns in prominent tourist regions. Policymakers should focus on sustainable economic growth by investing more on green technology through domestic investment and as well as attracting cleaner technologies from international trade activities